Fear but not fright: re-evaluating traumatic experience attenuates anxiety-like behaviors after fear conditioning - Costanzi, Marco; Saraulli, Daniele; Cannas, Sara; D’Alessandro, Francesca; Florenzano, Fulvio; Rossi-Arnaud, Clelia; Cestari, Vincenzo (Frontiers in Behavioral Neuroscience, 2014)
Fear allows organisms to cope with dangerous situations and remembering these situations has an adaptive role preserving individuals from injury and death. However, recalling traumatic memories can induce re-experiencing the trauma, thus resulting in a maladaptive fear. A failure to properly regulate fear responses has been associated with anxiety disorders, like Posttraumatic Stress Disorder (PTSD). Thus, re-establishing the capability to regulate fear has an important role for its adaptive and clinical relevance. Strategies aimed at erasing fear memories have been proposed, although there are limits about their efficiency in treating anxiety disorders. To re-establish fear regulation, here we propose a new approach, based on the re-evaluation of the aversive value of traumatic experience. Mice were submitted to a contextual-fear-conditioning paradigm in which a neutral context was paired with an intense electric footshock. Three weeks after acquisition, conditioned mice were treated with a less intense footshock (pain threshold). The effectiveness of this procedure in reducing fear expression was assessed in terms of behavioral outcomes related to PTSD (e.g. hyper-reactivity to a neutral tone, anxiety levels in a plus maze task, social avoidance, and learning deficits in a spatial water maze) and of amygdala activity by evaluating c-fos expression. Furthermore, a possible role of lateral orbitofrontal cortex (lOFC) in mediating the behavioral effects induced by the re-evaluation procedure was investigated. We observed that this treatment (i) significantly mitigates the abnormal behavioral outcomes induced by trauma, (ii) persistently attenuates fear expression without erasing contextual memory, (iii) prevents fear reinstatement, (iv) reduces amygdala activity and (v) requires an intact lOFC to be effective. The results suggest that an effective strategy to treat pathological anxiety should address cognitive re-evaluation of traumatic experiences mediated by lOFC